2020
DOI: 10.1002/solr.202000490
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylamine–Polystyrene Blends for Perovskite Solar Cells with Simultaneous Energy Loss Suppression and Stability Improvement

Abstract: Energy loss induced by nonradiative recombinations plays a critical role in determining power conversion efficiencies in perovskite solar cells, whereas device stability impacts their long‐time reliability in the ambient environment. It is an important challenge to suppress energy loss and improve device stability simultaneously. Herein, an interfacial layer of triphenylamine (TPA):polystyrene (PS) blend coated on the hybrid perovskite layer to concurrently suppress energy loss and improve device stability is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The typical (001) peak of 12.7° is assigned to the hexagonal PbI 2 phase, originating from the excessive PbI 2 in the perovskite film, as shown in Figure c, being consistent with the excess PbI 2 contained in the precursor solution . The characteristic peaks at 14.1 and 24.4° belong to the (110) and (111) planes of the tetragonal perovskite phase, respectively . Notably, there is no obvious shift in the perovskite diffraction angle, indicating that TBA cannot be embedded into a crystal lattice and can only accumulate ultimately at GBs .…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The typical (001) peak of 12.7° is assigned to the hexagonal PbI 2 phase, originating from the excessive PbI 2 in the perovskite film, as shown in Figure c, being consistent with the excess PbI 2 contained in the precursor solution . The characteristic peaks at 14.1 and 24.4° belong to the (110) and (111) planes of the tetragonal perovskite phase, respectively . Notably, there is no obvious shift in the perovskite diffraction angle, indicating that TBA cannot be embedded into a crystal lattice and can only accumulate ultimately at GBs .…”
Section: Resultsmentioning
confidence: 64%
“…37 The characteristic peaks at 14.1 and 24.4°belong to the (110) and (111) planes of the tetragonal perovskite phase, respectively. 38 Notably, there is no obvious shift in the perovskite diffraction angle, indicating that TBA cannot be embedded into a crystal lattice and can only accumulate ultimately at GBs. 39 It is found that the ratio of the (001) peak to the main peak (111) in the perovskite film decreases obviously, from 1.49 for the pristine perovskite to 0.95 for the TBA−perovskite sample, indicating that more PbI 2 precursors are transformed into the perovskite phase.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this device maintained 91% of its maximum efficiency for 10 days after storage under ambient conditions, which includes a relative humidity of 40-60%. 146 Recently, the p-type doped conducting polymer 9,9-dioctylfluorene-co-bis-N,N-((-4-butyl phenyl)-bis-N,N-phenyl-1,4-phenylenediamine) (PFB) was successfully employed as an HTM in PSCs. The highest PCE obtained for the fabricated n-i-p mesoscopic PSCs was 14.04%, which is 57% higher than that of the pristine PFB HTL.…”
Section: Pscs Built From Polymer Structures Containing Tpamentioning
confidence: 99%
“…Interestingly, this device maintained 91% of its maximum efficiency for 10 days after storage under ambient conditions, which includes a relative humidity of 40–60%. 146…”
Section: Triphenylamine Derivatives For Pscsmentioning
confidence: 99%